THE EFFECTS OF BACILLUS SUBTILIS CELLULASE ENZYME ON THE DECREASING OF CRUDE FIBER OF CASSAVA PEELS FOR FISH FOOD INGREDIENTS - Irma Melati; MasTri Djoko Sunarno (Pusbindiklat - LIPI, 2016)
The high content of crude fiber in cassava peel limits its digestion ability in fish. Cellulose enzyme from Bacillus subtilis is known to be able to degrade crude fiber. This study was aimed to obtain an effective dose of cellulase enzyme which was added to cassava peel to reduce its crude fiber content. The research was conducted in a completely randomized design with three treatments and two replications. The cellulase enzyme was extracted from Bacillus subtilis. Three different doses of the enzyme including control agent (0%, 25%, and 50%) were tested to degrade the crude fiber of cassava peels during two days of incubation period. Measured parameter is the fiber fraction of Neutral Detergent Fiber, Acid Detergent Fiber, lignin, cellulose, hemicellulose, reducing sugar, and soluble proteins. The data were analyzed using analysis of variance (F-test) and further with Duncan test to determine the mean difference between groups. The results of this study indicated that the most effective dose of cellulase enzyme to decrease the cassava peel crude fiber was 25%, in which the decrease of NDF, cellulose, and hemicellulose fractions were 16.27%, 18.04%, and 40.82% respectively, while reducing sugars and soluble protein contents increased into 57.50% and 38.94%, respectively.Our findings suggested that the addition of cellulose enzyme could improve cassava peels quality for fish food ingredients.